(untitled) (Global Journal of Human-Social Science, 2021)
Endogenous Nature of Socialization as a form of Social Progress-The Enlightenment produced the idea of social progress as a process that has a social dimension. Theoretical interpretation of social progress is attributed to the abbot of Saint-Pierre (1737 -France), whose contribution was analyzed in detail by A.Fet. Social progress has not only a social but also a personal dimension and represents a progress of personal self-development. While the social progress of society is associated with such social values as freedom, equality, security, etc., the progress of an individual is associated with its social component, with assessment of basic human needs, welfare, opportunities, which together allow to create the index of social progress, whose methodology was developed by a group of scientists led by M. Porter and presented in 2013 at the UN Ministerial Forum. The Social Progress Index is based on non-economic dimensions of social activities in terms of: provision of access to basic knowledge, information, communications, health, and ecosystem sustainability, which together constitute the basis of well-being and realization of opportunities (in terms of personal rights) for personal freedom and choice, tolerance and integration, as well as expanded education.